Life-Cycle Assessment in Agri-Food Systems and the Wine Industry—A Circular Economy Perspective - Catarina Marques; Sinem Güneş; Alice Vilela; Reinaldo Gomes (Foods)
Rapid population growth, climate change, and resource depletion pose significant challenges to global food production, demanding sustainable solutions. A Life-Cycle Assessment (LCA) provides a structured framework for evaluating the environmental impact of food systems throughout their entire life cycle. This review examines how an LCA can be integrated with circular economy principles to address sustainability challenges, optimize resource use, and minimize waste in food and alcoholic beverage production. A systematic review of LCA applications in the agri-food sector was conducted, analyzing studies published across different regions. The selection criteria included relevance to circular economy strategies, waste valorization approaches, and assessing environmental impacts using LCA methodologies. The analysis explores explicitly the synergy between food and wine production within the broader agri-food system, considering shared sustainability challenges and opportunities for resource optimization. Key methodologies include cradle-to-grave assessments and the evaluation of waste-to-resource technologies. The findings demonstrate that LCA effectively identifies critical environmental hotspots, enabling the implementation of eco-design and resource recovery practices. Circular strategies, such as the use of renewable energy, precision agriculture, and nutrient recovery, significantly enhance sustainability. However, gaps remain in accounting for social and regional variability, as well as in integrating advanced technologies. When combined with circular economy principles, LCA provides actionable insights for policy development and sustainable practices. Advancing LCA methodologies and fostering multi-stakeholder collaboration are essential for creating resilient and environmentally responsible agri-food systems.